Trust Building to Coordinate Collective Action in Reforestation Program - Witasari, Anna Indria (Jurnal Manajemen Hutan Tropika, 2017)
The study explores the way trust among agencies is established to coordinate collective action in rehabilitating protected areas, which have been utilized, commodified, and settled. Using an ethnography approach, the fieldwork was conducted in the villages surrounding 2 protected areas of West Lampung and South Lampung Districts in Lampung Province of Indonesia. There are several factors which hinder trust building process i.e. past experiences in relation to eviction from protected areas, forest policies which are not consistent, forest status which is protected areas, and the attitude of forest officers which consider land users as has no responsibility for conservation. Among those factors, forest policies which discursively and materially incorporate trust-building are the main factors which may help forest land rehabilitation process. Trust building process through negotiation where prejudice is turned into understanding among agencies still offer the possibility for forest rehabilitation efforts in the context of commodified landscape, agrarian change, and migration. However, negotiation is established through ’give and take’ mechanisms, trial and error, and a learning process. Landscape transformation where forest land rehabilitation occurs relies on the ’art’ of ’negotiation’ at a local level.